United Kingdom : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper examines the factors determining housing prices in the United Kingdom. Based on econometric evidence, the paper assesses whether recent housing price increases can be explained by fundamentals or whether they represent a temporary overshooting of housing prices, characteristic of a bubble. The paper estimates a simple error-correction model that describes the dynamics of real housing prices since the 1970s. Estimation results suggest that earnings and interest rates are the key determinants of housing prices, and that changes in real housing prices exhibit a large degree of persistence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet